Contrast enhanced ultrasound features of hepatic cystadenoma and hepatic cystadenocarcinoma. (4th March 2017) - Dong, Yi; Wang, Wen-Ping; Mao, Feng; Fan, Mei; Ignee, Andre; Serra, Carla; Sparchez, Zeno; Sporea, Ioan; Braden, Barbara; Dietrich, Christoph F.
Abstract: Objective: Hepatic (biliary) cystic tumor (HBCT) is a rare focal cystic liver lesion, which has been rarely described in the literature. In our current multicenter, retrospective study, we aimed to analyze contrast enhanced ultrasound (CEUS) features and its diagnostic performance in histologically proved HBCT. Material and methods: Twenty-three patients with single HBCT were retrospectively analyzed. Histologically, 17 (73.9%) were benign hepatic (biliary) cystadenoma (HBCA), 6 (26.1%) were hepatic (biliary) cystadenocarcinoma (HBCAC). All CEUS examinations were assessed by two independent radiologists in consensus. Criteria of CEUS imaging evaluation included the contrast enhancement pattern of lesion (hypoenhancing, hyperenhancing, isoenhancing in comparison to the surrounding liver parenchyma) during the arterial, portal venous and late phases. Results: After injection of ultrasound contrast agents, most of the HBCTs (78.3%, 18/23) had typical honeycomb enhancement pattern of the cystic wall, septa or mural nodules. Comparing between HBCA and HBCAC, hyperenhancement of the honeycomb septa during the arterial phase was more common in HBCA ( p  = .047). However, hypoenhancement during the portal venous and late phases was the characteristic of HBCAC ( p  = .041). Conclusions: The EFSUMB algorithm for CEUS for characterization of solid focal liver lesions is also applicable to HBCT. CEUS evaluation can avoid further diagnostic investigations or invasive biopsy procedure.